Determinan Tingkat Pengangguran : Peran Infasi dan Upah Minimum Di Provinsi Sumatera Utara Tahun 2009 Sampai 2023 - Syarifah Syarifah; Dhea Amanda; Nur Indah Melani Aruan; Monalisa Lumbantobing; Dodi Jese Rianto Siburian (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
High unemployment has become a significant issue in the province, which has great economic potential but faces challenges in reducing unemployment. In this analysis, economic and employment data of North Sumatra Province during the period were used to understand the relationship between inflation, minimum wage, and unemployment rate. The results of the analysis show that inflation has a significant influence on the unemployment rate in North Sumatra Province. High inflation can reduce people's purchasing power and create uncertainty in the labor market. In addition, the study also found that the minimum wage plays an important role in influencing the unemployment rate. Setting a minimum wage that is unbalanced or too high compared to labor productivity can limit the growth of new jobs.